TEORI AGENCY DALAM PERSEPEKTIF SOSIAL BUDAYA - Kamilia, Ibna; Fitriya, Elok (POLITEKNIK LP3I JAKARTA, 2023)
Agency tehory assumes that the principal and agent have different purposes, concerned with their utility and have different risk preferences. This study assumes that cultural diffrences will give a different color in the agency theory. Culture can align objectives between principle and agent, change their risk preferences and reduce opportunistic actions. Based on these arguments will be deve;oped some proporsitions which are expected to be tested empirically.Keywords : Agency Theory, Culture, Behavior